2006
DOI: 10.1007/s10533-005-4329-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Aspects of Dissolved Organic Carbon Leached from Senescent Plants in an Oligotrophic Wetland

Abstract: We conducted a series of experiments whereby dissolved organic matter (DOM) was leached from various wetland and estuarine plants, namely sawgrass (Cladium jamaicense), spikerush (Eleocharis cellulosa), red mangrove (Rhizophora mangle), cattail (Typha domingensis), periphyton (dry and wet mat), and a seagrass (turtle grass; Thalassia testudinum). All are abundant in the Florida Coastal Everglades (FCE) except for cattail, but this species has a potential to proliferate in this environment. Senescent plant samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 60 publications
7
87
0
Order By: Relevance
“…3; Table 1), suggesting that the CDOM in FB is not substantially derived from the freshwater marshes or the fringe mangroves in the Everglades, but instead probably produced in FB directly or indirectly by seagrass/phytoplankton community. This interpretation is in agreement with previous reports (Maie et al, 2005;Maie et al, 2006) and further supported by the d 13 C value of high molecular weight fraction of DOM collected from the FB, which is significantly heavier ($)14&) than that from the Everglades ($)27&) (Maie, personal communication). The longer k max values for all regions during the wet season compared to the dry season suggest a higher input of terrestrial DOM from the Everglades during wet season.…”
Section: Qualitative Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…3; Table 1), suggesting that the CDOM in FB is not substantially derived from the freshwater marshes or the fringe mangroves in the Everglades, but instead probably produced in FB directly or indirectly by seagrass/phytoplankton community. This interpretation is in agreement with previous reports (Maie et al, 2005;Maie et al, 2006) and further supported by the d 13 C value of high molecular weight fraction of DOM collected from the FB, which is significantly heavier ($)14&) than that from the Everglades ($)27&) (Maie, personal communication). The longer k max values for all regions during the wet season compared to the dry season suggest a higher input of terrestrial DOM from the Everglades during wet season.…”
Section: Qualitative Parameterssupporting
confidence: 92%
“…DOM with different C:N ratios reflect different DOM sources and/or diagenetic processing (e.g., DOM originating from higher plants has greater C:N values than DOM from microbes; Caraco & Cole, 2003;McKnight et al, 2003). A high C:N ratio during the wet season in the FCE estuaries may be due to a large contribution of DOM freshly leached from senescent plant biomass (Maie et al, 2006).…”
Section: Regional Dom Variabilitymentioning
confidence: 99%
“…The phenolic and lignin content of EC was less than half of TD from both the greenhouse experiment and the marshes. In a related study, Maie et al (2006) found that litter of TD leached about 4× more phenolics than litter of Eleocharis sp. Apparently, the lower concentration of these compounds in EC as compared to TD is a result of genetic differences between the species.…”
Section: Discussionmentioning
confidence: 90%
“…As far as we know, THM-GC-MS has not been applied to P. oceanica materials yet. Kristensen et al (2009) analyzed an undefined seagrass, while Maie et al (2006) analyzed leachates from turtle grass (i.e.…”
Section: Introductionmentioning
confidence: 99%